The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1007/bf00258740
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state sodium absorption and chloride secretion of colon and coprodeum, and plasma levels of osmoregulatory hormones in hens in relation to sodium intake

Abstract: The plasma levels of four osmoregulatory hormones and their target ion-transport systems in the lower intestines of the domestic fowl were determined in order to elucidate their interrelationship and their setpoints in relation to NaCl intake. White Plymouth Rock hens were adapted to six intake levels of NaCl (0.20 +/- 0.02-24.7 +/- 1.9 mmoles Na+.kg bw-1.day-1) for 6 weeks. The Na+ absorption and the Cl- secretion of colon and coprodeum were characterized in vitro by the effects of hexoses, amino acids, amilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 28 publications
5
26
0
Order By: Relevance
“…The response of brush cells to resalination and aldosterone stimulation is very quick and occurs within 1-2 days. It can be concluded that the changes are closely related to measured variations in sodium transport (as observed in this study) and plasma-aldosterone level, as shown by Arnason et al (1986), Arnason and Skadhauge (1991), Thomas and Skadhauge (1982), and Skadhauge et al (1983).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The response of brush cells to resalination and aldosterone stimulation is very quick and occurs within 1-2 days. It can be concluded that the changes are closely related to measured variations in sodium transport (as observed in this study) and plasma-aldosterone level, as shown by Arnason et al (1986), Arnason and Skadhauge (1991), Thomas and Skadhauge (1982), and Skadhauge et al (1983).…”
Section: Discussionsupporting
confidence: 79%
“…Plasma concentrations of Na + , Cl -, and K + , measured in previous studies (Thomas and Skadhauge 1982;Skadhauge et al 1983;Arnason et al 1986;Arnason and Skadhauge 1991) and in this study of aldosterone stimulation, expressed a slight temporary interruption of homeostasis, which seemed to be reestablished within the experimental period. In the present study, development of the dome-like cell apices, most pronounced after 2-3 days of resalination and 2-4 days of aldosterone stimulation, might reflect this temporary interruption of homeostasis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…1); high-Na¤ fed birds have a low serum aldosterone concentration, as previously described ( Arnason & Skadhauge, 1991;Garriga et al 1999a). When animals that had been maintained for 14 days in the low-Na¤ diet (L14d group) were resalinated, the serum aldosterone concentration returned to the values characteristic of the highNa¤ condition within 4 h of the oral NaCl dose (R4h group).…”
Section: Animal Modelmentioning
confidence: 83%
“…However, both dehydration ( [2] and current results) and Na + depletion [19] increase plasma aldosterone levels. Since it has been reported that the plasma arginine vasotocin (AVT) level is increased by dehydration [2] and decreased by Na + depletion [1], AVT could be the regulator of intestinal Na + -dependent sugar transport. We have not been able to measure plasma AVT levels in the chicken.…”
Section: Discussionmentioning
confidence: 99%